The effect of cardiorespiratory fitness training on developing speed endurance, heart rate adaptation, and men’s 1500-meter running performance - F.M. Al – Dulaimi , Rana; Easa , Fahem (Journal of Physical Education, 2024)
The problem of the research is that there is a weakness in speed endurance, which has a direct impact on achievement, as it leads to early fatigue, lack of concentration, and a low level of effectiveness of performance, which made the researchers interested in this problem and finding solutions to it. Hence the importance of the research is evident: preparing cardiorespiratory fitness training to develop speed endurance and rate adaptation. The heartbeat that occurs in runners is a continuous result of training and the use of a type of training that suits the requirements of the 1500-meter running competition. The researchers used the experimental approach with pre- and post-testing for the experimental and control groups. The research community was identified as players in the 1500-meter competition for the elite men’s category of the Iraqi Athletics Federation for the 2024 sports season. The number of them was (12 players), and the sample was divided into two groups, the experimental group and the control group, with (6 players) for each group. The researchers concluded that the results showed a noticeable superiority between the pre- and post-measurement of cardio-respiratory fitness training to develop speed endurance and adaptation of heart rate and achievement for the experimental group and in favor of the post-measurement. The researchers recommended conducting similar studies and research on different age groups.